Situation Report: Hungary, 25 March 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Seventh Patriotic People's Front Congress Highlighted by Kadar Address Houses of Culture Are Slow to Adapt to Social Needs Young Writers' Group Dissolved Hungary Confirms Flexible Exchange Rate Policy by Devaluing the Forint Conversion of Abandoned Village Homes into Dachas Encouraged New Rules Governing Apartments Rented and Sold by Local Councils Weak Agricultural Cooperatives' Efforts to Enlist High Class Experts Cooperatives' Ancillary Work Fills Gap for Economy and Armed Forces Centennial of Bela Bartok's Birth